A novel fluorescein-bisphosphonate based diagnostic tool for the detection of hydroxyapatite in both cell and tissue models. Issue 1 (December 2018) - Sim, Alisia; Rashdan, Nabil; Cui, Lin; Moss, Alastair; Nudelman, Fabio; Dweck, Marc; MacRae, Vicky; Hulme, Alison
Abstract A rapid and efficient method for the detection of hydroxyapatite (HAP) has been developed which shows superiority to existing well-established methods. This fluorescein-bisphosphonate probe is highly selective for HAP over other calcium minerals and is capable of detecting lower levels of calcification in cellular models than either hydrochloric acid-based calcium leaching assays or the Alizarin S stain. The probe has been shown to be effective in bothin vitro vascular calcification models andin vitro bone calcification models. Moreover we have demonstrated binding of this probe to vascular calcification in rat aorta and to areas of microcalcification, in human vascular tissue, beyond the resolution of computed tomography in human atherosclerotic plaques. Fluorescein-BP is therefore a highly sensitive and specific imaging probe for the detection of vascular calcification, with the potential to improve not onlyex vivo assessments of HAP deposition but also the detection of vascular microcalcification in humans.